History and iconography of Grigor Narekats i’s vision - V. Devrikyan; Sh. Devrikyan (Шаги, 2023)
The great Armenian poet Grigor Narekatsi (Gregory of Narek; venerated as a saint of the Armenian Apostolic and Catholic Churches and declared a Doctor of the Church by Pope Francis in 2015) was canonized and numbered among the saints of the Armenian Church thanks to his poem “Book of Lamentations”. His Vita, rich with tales about his miracles, arose within the framework of medieval Armenian literature. One of the most striking episodes of his Life is the legend which tells that one day during self-forgetful prayer, in a vision Narekatsi saw the Mother of God holding the Christ Child in her arms. As confirmation of the historical veracity of Narekatsi’s vision lines from his works are cited in the Vita. This episode from the Life was widely disseminated by means of oral retelling and was also presented as a separate wonder narrative. At the same time, among the images related to Narekatsi, his vision has also been illustrated more than any other, both in Armenian manuscripts and in the engravings in early printed books. The article traces the gradual development of this iconographic form, from the marginal and page miniatures of the manuscripts to the engravings of the two printed commentaries (1745, 1801) dedicated to the “Book of Lamentations”.